PENGARUH PENGGUNAAN METODE PROYEK TERHADAP HASIL BELAJAR BIOLOGI PADA MATERI POKOK STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN DI KELAS X SMA NEGERI 1 BATANG ANGKOLA (Jurnal TAROMBO, 2019)
The aim of this research was to know whether there was any significant influence of using project method toward IPA achievement in the structure and function of tissue plants at the eighth grade students of SMA Negeri 1 Batang Angkola. The method of this research was descriptive. By using cluster sampling technique, the writer took 46 students as the sample. Questionnaire was used collect the data of using project method and test for the structure and function of tissue plants subject. Based on descriptive analysis, the average of using project method was 2.88, it was categorized “good” and the average of the structure and function of tissue plants subject was 70.33, it was categorized “good”. Based statistic inferential analysis by using ttest to test hypothesis, it could be gotten tcount = 3.61 and ttable = 1.678 at error level 5%. It could be seen tcount was greater than ttable (3.61>1.678). It means alternative hypothesis was accepted. In the other words, there was any significant influence of using project method toward IPA achievement in the structure and function of tissue plants at the eighth grade students of SMA Negeri 1 Batang Angkola.